Molecular characters and different expression of WRKY1 gene from Gossypium barbadense L. and Gossypium hirsutum L. Issue 6 (1st November 2016) - Liu, Jianfeng; Dong, Lijun; Liu, Haoran; Li, Yanli; Zhang, Kaijian; Gao, Suwei; Zhang, Tonghui; Zhang, Shuling
ABSTRACT: Cotton is one of the most important economic crops in the world. Gossypium barbadense L. has higher resistance to Verticillium wilt than Gossypium hirsutum L. In the present study, seedlings of Pima90-53 ( G. barbadense ) had better growth performance than those of CRI8 ( G. hirsutum ) inoculated with Verticillium dahliae . WRKY1 genomic DNA of Pima90-53 and CRI8 were isolated ( GbWRKY1 and GhWRKY1 ) and predicted to include three introns which were 289, 92, 87 bp and 286, 92, 87 bp in length, respectively. Compared with the DNA sequence of GbWRKY1, GhWRKY1 had a 13-base deletion in exon 4, which resulted in premature termination of translation. It was predicted that the GbWRKY1 and GhWRKY1 proteins contain two WRKY domains and zinc-finger motifs belonging to group I WRKY proteins. Two promoters, located 1745 bp and 1738 bp upstream of GbWRKY1 and GhWRKY1, were cloned and predicted to contain important regulatory elements (TATA-box, CAAT-box and pathogen/elicitor-related elements). Interestingly, compared with GbWRKY1, the GhWRKY1 promoter lacked an ethylene-responsive element (ERE) component. The relative expression of GbWRKY1, too, was higher than that of GhWRKY1 after V. dahliae and ACC (1-aminocyclopropane-1-carboxylic acid) induction. The results suggest that the difference in the promoter sequence could probably be one of the reasons that lead to different expression patterns and resistance to Verticillium wilt in Pima90-53 and CRI8.